KONSEP PEMBELIAN KOMPULSIF: SEBUAH KETERPAKSAAN - A - Alfitman; Basu Swastha Dharmmesta; Bayu Aji Aritejo (Universitas Mercu Buana, 2021)
Until 2020, there is no consensus among researchers about the actual compulsive buying concept is. There are many different compulsive buying concepts in the scientific literature (Ridgway et al., 2008; Goldsmith et al., 2015). Consequently, it is difficult for marketers to implement it in marketing decision making. This study aims to clarify it by categorizing any existing compulsive buying concepts in scientific literature and offer one of which for the best explanation. Based on a literature study, we collected data from any scientific research in any discipline. By using bibliometric analysis, the concept of compulsive buying can categorize it into three categories: compulsive buying as a disease, as a bad habit or